2014
DOI: 10.1111/joes.12062
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Regional Economic Impacts of Defense Activities: A Survey of Methods

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…The study further examined the long-run effect of all variables on the military expenditure (i.e., taking ME as dependent variable) and safely concluded that there is a significant and negative relationship between ME and Unemp in SAARC region. These results is consistent with the previous studies of Paul (1996), Hou and Chen (2014), Pereira and Andraz (2014), Droff and Paloyo (2014) etc. All of the studies confirmed the significant association between unemployment rate and military spending across the globe.…”
Section: Resultssupporting
confidence: 96%
“…The study further examined the long-run effect of all variables on the military expenditure (i.e., taking ME as dependent variable) and safely concluded that there is a significant and negative relationship between ME and Unemp in SAARC region. These results is consistent with the previous studies of Paul (1996), Hou and Chen (2014), Pereira and Andraz (2014), Droff and Paloyo (2014) etc. All of the studies confirmed the significant association between unemployment rate and military spending across the globe.…”
Section: Resultssupporting
confidence: 96%
“…An example is the closure of a military base, which is usually the main employer, in a small town (for a survey, see Droff and Paloyo [2014]). …”
Section: Identification Of Neighborhood Effectsmentioning
confidence: 99%